Multiple Novel Mosquito-Borne Zoonotic Viruses Revealed in Pangolin Virome - Zhang, Duo; Zheng, Min; Zhang, Ying; Feng, Guanrong; Peng, Chengcheng; Li, Chenghui; Li, Yiquan; Zhang, He; Li, Nan; Xiao, Pengpeng (Frontiers in Cellular and Infection Microbiology, 2022)
Swab samples were collected from 34 pangolins in Guangxi province, China. Metavirome sequencing along with bioinformatics approaches were undertaken to determine the abundant virus sequences in their viromes, the results showed that virus sequences pertained to 24 virus taxonomic families. To identify the results, PCR combined with phylogenetic analysis was conducted. Some viral sequences covering Japanese encephalitis virus (JEV), Getah virus (GETV) and Chikungunya virus (CHIKV) were detected. On the basis of metavirome analysis, seven segments belonging to JEV were further identified through PCR amplification. Sequence comparison showed that among seven sequences, JEV-China/P2020E-1 displayed the highest nucleotide (80.6%) with the JEV isolated in South Korea, 1988, and all of which were belonging to III genotype. Seven CHIKV sequences were detected with the highest homologous (80.6%) to the Aedes africanus in Cote d'ivoire, 1993. And passing from BHK-21 to Vero make the newly isolated CHIKV-China/P2020-1 more contagious. Besides, newly verified GETV sequences shared 86.4% identity with the 1955 GETV isolated from Malaysia. Some sudden and recurrent viruses were also observed from the virome of pangolin in Guangxi province, China, hence, dissemination tests will be implemented in the future.